Mesh Enhancement of a 3D Volumetric Model using Generative AI for a Web 3.0-based Graphic Service - Park, Byung-Seo; Jang, Ye-Won; Lee, Hak-Bum; Seo, Young-Ho (Journal of Web Engineering, 2025)
Using depth images from RGB-D cameras simplifies reconstructing 3D information for adaptive online transmission. However, depth sensors often produce distance-related distortions, leading to 3D distortions in reconstructed point clouds or meshes. This paper addresses these issues by proposing a method to enhance volumetric 3D data quality using synthesized point clouds and generating meshes with low-cost RGB-D cameras for Web 3.0 graphic services. We utilize calibration and reconstruction techniques from previous studies to create point clouds, refine them, and convert them into meshes. Finally, we improve the mesh surface using a latent diffusion model (LDM). The proposed calibration method reduced errors to 0.00926 mm in the 3D Charuco board experiment. For the Moai statue, the alignment accuracy achieved an average error of 8 mm and a standard deviation of 3.9 mm. Using LDM, the mesh surface improvement reduced the average error by 54.8% and the standard deviation by 65.9%.